Antibacterial ceramic and preparation method thereof
By preparing composite hydroxyapatite in ceramics and loading silver ions and copper ions, the problems of uneven dispersion of antibacterial agents and insufficient antibacterial durability are solved, and efficient and long-lasting antibacterial effects and good physical and mechanical properties are achieved.
Patent Information
- Application Number
- CN202510064312.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-15
AI Technical Summary
In the existing antibacterial ceramic preparation process, the dispersion of antibacterial agents affects the antibacterial durability and effect of the ceramics. They are also costly, the antibacterial agents are prone to oxidation and inactivation, and excessive dissolution of silver ions harms the human body.
Complex hydroxyapatite was prepared by hydrothermal method, and titanium dioxide was generated on it in situ to improve antibacterial properties. Then 5-thiazole carboxylate was introduced on the composite hydroxyapatite, and silver ions and copper ions were loaded through the chelation reaction, making them stronger in combination with hydroxyapatite, thereby improving antibacterial durability.
The excellent antibacterial properties and antibacterial durability of antibacterial ceramics are achieved, the preparation cost is reduced, the problem of excessive dissolution of silver ions is avoided, and the physical and mechanical properties of the ceramics are ensured.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic products, and in particular relates to an antibacterial ceramic and a preparation method thereof. Background Art
[0002] Ceramics are mainly made by firing mineral clay and inorganic salt raw materials. During the preparation process, the raw materials are first mixed and formed, and then fired through a high-temperature process. Ceramics are widely used due to their advantages such as good stability, high temperature resistance, corrosion resistance and good insulation. There are many types of ceramics, such as ceramic handicrafts, electrical ceramics, daily ceramics, architectural ceramics, etc. Different fields have different performance requirements for ceramics.
[0003] Due to the high development and progress of science and technology, human beings have higher and higher requirements for the performance, quality and performance of ceramic materials, which has promoted the birth of functional ceramics. There are many types of functional ceramics. Based on the different requirements of various industries for ceramic functions, functional ceramics are given various mechanical, thermal, chemical, electrical, magnetic, optical, radiation and biological functions. Among them, antibacterial ceramics are ceramic products with antibacterial functions. As functional ceramic products, antibacterial ceramics can effectively prevent various infectious diseases from invading humans, especially in some relatively humid and noisy places where bacteria are more likely to breed, such as kitchens, washrooms, toilets, public places, hospitals, etc., because of the large flow of people, bacteria are more likely to multiply and spread.
[0004] The existing process for preparing antibacterial ceramics is mostly to directly add antibacterial agents to the glaze raw materials and then fire them. However, due to the poor compatibility of the antibacterial agents with the glaze raw materials, the antibacterial agents are unevenly dispersed in the glaze and are prone to agglomeration, which affects the antibacterial durability of the final ceramic products and cannot achieve the expected antibacterial effect. Some technicians achieve the antibacterial effect by coating the ceramic glaze with an antibacterial coating. However, since the glaze is not wear-resistant and the bonding strength between the antibacterial coating and the glaze is not high, the antibacterial coating will be worn away quickly, thereby losing its corresponding function.
[0005] Chinese patent application CN110818261A discloses an antibacterial ceramic glaze and its preparation method and application. The raw material components include ceramic glaze, antibacterial agent, suspending agent and degumming agent; the antibacterial agent is a mixture of nano zirconium silicate silver and nano zinc oxide. According to the weight percentage of the dry weight of the ceramic glaze, the addition amount of the nano zirconium silicate silver is 2-6%, and the addition amount of the nano zinc oxide is 0.05%-2%; the suspending agent is a mixture of low-viscosity sodium carboxymethyl cellulose and medium-viscosity sodium carboxymethyl cellulose, and the degumming agent is one of sodium tripolyphosphate or sodium metasilicate. The ceramic glaze prepared by the invention can achieve uniform dispersion of the antibacterial agent in the ceramic tile surface glaze, and has efficient bactericidal and antibacterial effects and stable sustainable bactericidal effects. However, it has the problems of high cost, easy oxidation and inactivation of the antibacterial agent, excessive dissolution of silver ions that harm the human body, and short antibacterial duration.
[0006] Chinese patent application CN113213903A discloses an environmentally friendly antibacterial ceramic blank and its processing technology, wherein the environmentally friendly antibacterial ceramic blank comprises the following component groups: 40-50 parts of SiO2, 20-35 parts of Al2O3, 3-5 parts of K2O, 2-8 parts of Li2O, 2-4 parts of Fe2O3, 3-10 parts of CaO, 3-7 parts of TiO2, 4-6 parts of MgO, 5-8 parts of Na2O, 25-40 parts of kaolin, 15-25 parts of quartz powder, 10-15 parts of antibacterial agent, and 2-5 parts of binder. The environmentally friendly antibacterial ceramic blank and its processing technology provided by the invention have high stability and mechanical strength through the combination of the above components, and the raw materials are easy to obtain, environmentally friendly, and have strong antibacterial properties. However, its antibacterial effect is limited and it cannot be continuously antibacterial, which needs to be further improved.
[0007] Therefore, it is of great application value to develop an antibacterial ceramic with good antibacterial effect, good antibacterial durability and good mechanical properties in this field. Summary of the invention
[0008] In view of the deficiencies in the prior art, an object of the present invention is to provide an antibacterial ceramic and a preparation method thereof.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A method for preparing an antibacterial ceramic comprises the following steps:
[0011] S1. Preparation of composite hydroxyapatite: Na2HPO4 is added to deionized water, and then ammonia water is added to adjust the pH to 11-12 to obtain solution A; Ca(NO3)2 is added to deionized water to obtain solution B; solution B is added dropwise to solution A under stirring, and ammonia water is added during the addition to maintain the pH at 10-11. After the addition is completed, tetrabutyl titanate ethanol solution is added to carry out a hydrothermal reaction. After the reaction is completed, the mixture is filtered, washed, and dried to obtain composite hydroxyapatite;
[0012] S2. Preparation of a composite antibacterial agent: adding composite hydroxyapatite to an ethanol aqueous solution, then adding γ-aminopropyltriethoxysilane, stirring to react, adding 5-thiazolecarboxaldehyde and triethylamine after the reaction is completed, and reacting at a constant temperature under a nitrogen atmosphere, filtering, washing, and drying after the reaction is completed to obtain a solid product; then adding the solid product to deionized water, then adding silver nitrate and copper nitrate, adjusting the pH to 6-7, and performing a chelating reaction, filtering, drying, and calcining after the reaction is completed to obtain a composite antibacterial agent;
[0013] S3, preparation of ceramic body: kaolin, quartz, dolomite, alumina, potassium carbonate, calcium carbonate, diatomaceous earth, magnesium oxide, silicon carbide whisker, borax, composite antibacterial agent and water are uniformly mixed, wet ball milled to obtain body slurry, then pressed into shape, and dried to obtain ceramic body;
[0014] S4, preparation of glaze slurry: potassium feldspar, sodium feldspar, quartz, magnesite, calcite, zinc oxide, illite, talc, zirconium silicate, composite antibacterial agent, sodium carboxymethyl cellulose and water are mixed evenly, and wet ball milled to obtain glaze slurry;
[0015] S5, glazing and sintering: glazing the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping to obtain a glaze layer, drying and then sintering, and naturally cooling to obtain the antibacterial ceramic.
[0016] Preferably, in step S1, the concentration of solution A is 0.5-0.7 mol / L, the concentration of solution B is 0.8-1 mol / L, the mass concentration of ammonia water is 10-15%, the concentration of tetrabutyl titanate ethanol solution is 0.1-0.15 mol / L, and the volume ratio of solution A, solution B, and tetrabutyl titanate ethanol solution is 60-70:100-120:30-40.
[0017] Preferably, the temperature of the hydrothermal reaction in step S1 is 130-140° C. and the time is 6-8 h.
[0018] In the present invention, hydroxyapatite is prepared by a hydrothermal method, and tetrabutyl titanate is added during the preparation process to generate titanium dioxide in situ on the hydroxyapatite, which can improve the antibacterial property of hydroxyapatite on the one hand, and on the other hand, make the prepared composite hydroxyapatite have a complex surface structure, so that the silver ions and copper ions subsequently loaded are more stable.
[0019] Preferably, the volume concentration of ethanol in the ethanol aqueous solution in step S2 is 60-70%, the mass ratio of the composite hydroxyapatite, γ-aminopropyltriethoxysilane, 5-thiazolecarboxaldehyde, and triethylamine is 50-60:10-13:5-7:20-25, the temperature of the stirring reaction is 65-70°C, the time is 1-2h, and the temperature of the constant temperature reaction is 70-75°C, and the time is 2-3h.
[0020] Preferably, in step S2, the mass ratio of the solid product, deionized water, silver nitrate and copper nitrate is 50-60:800-900:5-8:3-5, the temperature of the chelating reaction is 70-80°C, and the time is 5-7h; the temperature of the calcination is 600-700°C, and the time is 1-2h.
[0021] In the present invention, 5-thiazole carboxaldehyde is introduced into the composite hydroxyapatite through the action of chemical bonds. The nitrogen atoms and sulfur atoms contained in 5-thiazole carboxaldehyde can serve as coordinating atoms to form chelates with silver ions and copper ions, thereby enhancing the binding force between the metal ions and the composite hydroxyapatite. After the calcination process, the hydroxyapatite is firmly bound to the silver ions and copper ions, thereby significantly improving the antibacterial durability of the antibacterial ceramic.
[0022] Preferably, in step S3, the amount of each raw material is as follows, by weight: 30-40 parts of kaolin, 20-25 parts of quartz, 15-20 parts of dolomite, 10-15 parts of alumina, 2-3 parts of potassium carbonate, 1-2 parts of calcium carbonate, 5-8 parts of diatomaceous earth, 3-6 parts of magnesium oxide, 3-5 parts of silicon carbide whiskers, 2-5 parts of borax, 3-4 parts of composite antibacterial agent, and 35-45 parts of water; the rotation speed of the wet ball mill is 600-700r / min, and the time is 4-6h.
[0023] In the present invention, the ceramic body is composed of kaolin, quartz, dolomite and the like as the basic skeleton of the body, silicon carbide whiskers are used as reinforcing agents, and various fluxes such as potassium carbonate, calcium carbonate, borax, etc. improve the densification of the body, thereby enhancing the strength and toughness of the ceramic.
[0024] Preferably, in step S4, the amount of each raw material is as follows, by weight: 40-45 parts of potassium feldspar, 25-35 parts of sodium feldspar, 20-30 parts of quartz, 5-8 parts of magnesite, 10-15 parts of calcite, 8-12 parts of zinc oxide, 10-14 parts of illite, 5-10 parts of talc, 8-11 parts of zirconium silicate, 3-5 parts of composite antibacterial agent, 4-6 parts of sodium carboxymethyl cellulose, and 70-90 parts of water; the rotation speed of the wet ball mill is 800-900r / min, and the time is 7-8h.
[0025] In the present invention, potassium feldspar and sodium feldspar are used in the glaze to reduce the firing temperature, quartz is used to enhance the hardness and chemical stability, and various fluxes such as magnesite, calcite, zinc oxide, etc. are added to improve the fluidity and gloss, illite and talc are used to improve the chemical stability and thermal expansion coefficient, zirconium silicate is used to give it an opaque or translucent effect, and sodium carboxymethyl cellulose is used as a dispersant to improve the uniformity of glazing, thereby ensuring the hardness, wear resistance and antibacterial properties of the ceramic surface.
[0026] Preferably, the thickness of the glaze layer in step S5 is 0.5-0.8 mm.
[0027] Preferably, the sintering process in step S5 is: in an inert atmosphere, heating to 400-500°C at a heating rate of 3-5°C / min, keeping warm for 2-4h, and then heating to 1200-1250°C at a heating rate of 6-8°C / min for 3-5h.
[0028] The present invention also protects an antibacterial ceramic prepared by the method as described above.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The antibacterial ceramic provided by the present invention has excellent antibacterial properties by adding a composite antibacterial agent to the ceramic body and glaze slurry, which can effectively inhibit the growth of bacteria. At the same time, the composite antibacterial agent is prepared by a specific method, which improves the antibacterial durability of the antibacterial ceramic. It can be widely used in medical and health, food processing, home life and other fields, and has broad application prospects.
[0031] (2) The antibacterial ceramic provided by the present invention is used to prepare the composite antibacterial agent. Hydroxyapatite is prepared by a hydrothermal method. Tetrabutyl titanate is added during the preparation process to generate titanium dioxide in situ on the hydroxyapatite. On the one hand, the antibacterial property of the hydroxyapatite can be improved. On the other hand, the prepared composite hydroxyapatite has a complex surface structure, which makes the silver ions and copper ions loaded later more stable. Subsequently, the composite hydroxyapatite is modified by using γ-aminopropyltriethoxysilane to introduce active amino groups into the hydroxyapatite. Then, the composite hydroxyapatite is treated by a molten-crystal method. Through the Schiff base reaction, 5-thiazolecarboxaldehyde is introduced into hydroxyapatite, and finally the silver ions and copper ions are loaded into the hydroxyapatite through the chelation reaction. The nitrogen atoms and sulfur atoms contained in the introduced 5-thiazolecarboxaldehyde can act as coordinating atoms to form chelates with silver ions and copper ions, which can not only enhance the binding force between metal ions and composite hydroxyapatite, but also load more silver ions and copper ions. After the calcination process, the hydroxyapatite is more firmly bound to the silver ions and copper ions, thereby significantly improving the antibacterial durability of the antibacterial ceramic.
[0032] (3) The antibacterial ceramic provided by the present invention adopts a ceramic body and glaze slurry with a specific formula, and uses a specific sintering process to fully sinter the body to achieve an optimal densification degree, so that the prepared antibacterial ceramic has good physical and mechanical properties. At the same time, silicon carbide whiskers are added to the body to improve the strength and hardness of the ceramic, as well as good wear resistance and corrosion resistance, thereby ensuring its reliability and stability in various application scenarios. DETAILED DESCRIPTION
[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0034] A method for preparing an antibacterial ceramic comprises the following steps:
[0035] S1. Preparation of composite hydroxyapatite: Na2HPO4 was added to deionized water, and then ammonia water with a mass concentration of 15% was added to adjust the pH to 12 to obtain a solution A with a concentration of 0.6 mol / L; Ca(NO3)2 was added to deionized water to obtain a solution B with a concentration of 0.9 mol / L; 200 mL of solution B was added dropwise to 330 mL of solution A under stirring conditions (stirring speed was 120 r / min), and ammonia water was added during the addition to maintain the pH at 11. After the addition was completed, 110 mL of 0.13 mol / L tetrabutyl titanate ethanol solution was added, and the mixture was hydrothermally reacted at 135°C for 7 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain composite hydroxyapatite;
[0036] S2. Preparation of composite antibacterial agent: 55g composite hydroxyapatite was added to 900mL ethanol aqueous solution (volume concentration of ethanol was 65%), followed by adding 12g γ-aminopropyltriethoxysilane, stirring and reacting at 70°C for 1h, adding 6g 5-thiazolecarboxaldehyde and 23g triethylamine after the reaction was completed, and reacting at a constant temperature of 73°C in a nitrogen atmosphere for 2.5h, filtering, washing and drying after the reaction was completed to obtain a solid product; then 55g of the solid product was added to 850g deionized water, followed by adding 7g silver nitrate and 4g copper nitrate, adjusting the pH to 7, and chelating at 75°C for 6h, filtering and drying after the reaction was completed, and calcining at 650°C in a nitrogen atmosphere for 1.5h to obtain a composite antibacterial agent;
[0037] S3, preparation of ceramic body: by weight, 35 parts of kaolin, 23 parts of quartz, 17 parts of dolomite, 13 parts of aluminum oxide, 2.5 parts of potassium carbonate, 1.5 parts of calcium carbonate, 7 parts of diatomaceous earth, 5 parts of magnesium oxide, 4 parts of silicon carbide whiskers, 4 parts of borax, 3.5 parts of composite antibacterial agent, 40 parts of water were mixed evenly, and wet ball milled at a speed of 650r / min for 5h to obtain body slurry, which was then pressed into shape and dried to obtain a ceramic body;
[0038] S4, preparation of glaze slurry: 43 parts of potassium feldspar, 30 parts of sodium feldspar, 25 parts of quartz, 7 parts of magnesite, 12 parts of calcite, 10 parts of zinc oxide, 12 parts of illite, 8 parts of talc, 10 parts of zirconium silicate, 4 parts of composite antibacterial agent, 5 parts of sodium carboxymethyl cellulose, and 80 parts of water were mixed evenly, and wet ball milled at a speed of 850 r / min for 7.5 h to obtain glaze slurry;
[0039] S5, glazing and sintering: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping to obtain a glaze layer with a thickness of 0.7 mm. After drying at 105°C, sintering is performed. The sintering process is as follows: in an inert atmosphere, heating to 450°C at a heating rate of 4°C / min, keeping the temperature for 3 hours, then heating to 1230°C at a heating rate of 7°C / min for 4 hours, and naturally cooling to obtain the antibacterial ceramic. Example 2
[0040] A method for preparing an antibacterial ceramic, characterized in that it comprises the following steps:
[0041] S1. Preparation of composite hydroxyapatite: Na2HPO4 was added to deionized water, and then ammonia water with a mass concentration of 10% was added to adjust the pH to 11 to obtain a solution A with a concentration of 0.6 mol / L; Ca(NO3)2 was added to deionized water to obtain a solution B with a concentration of 0.9 mol / L; 190 mL of solution B was added dropwise to 320 mL of solution A under stirring conditions (stirring speed was 110 r / min), and ammonia water was added during the addition to maintain the pH at 10. After the addition was completed, 100 mL of 0.12 mol / L tetrabutyl titanate ethanol solution was added, and the mixture was hydrothermally reacted at 135°C for 7 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain composite hydroxyapatite;
[0042] S2. Preparation of composite antibacterial agent: 55g composite hydroxyapatite was added to 900mL ethanol aqueous solution (volume concentration of ethanol was 65%), followed by adding 11g γ-aminopropyltriethoxysilane, stirring and reacting at 65°C for 2h, adding 6g 5-thiazolecarboxaldehyde and 23g triethylamine after the reaction was completed, and reacting at a constant temperature of 73°C in a nitrogen atmosphere for 2.5h, filtering, washing and drying after the reaction was completed to obtain a solid product; then 55g of the solid product was added to 850g deionized water, followed by adding 6g silver nitrate and 4g copper nitrate, adjusting the pH to 7, and chelating at 75°C for 6h, filtering and drying after the reaction was completed, and calcining at 650°C in a nitrogen atmosphere for 1.5h to obtain a composite antibacterial agent;
[0043] S3, preparation of ceramic body: by weight, 35 parts of kaolin, 22 parts of quartz, 18 parts of dolomite, 15 parts of aluminum oxide, 2.5 parts of potassium carbonate, 1.5 parts of calcium carbonate, 6 parts of diatomaceous earth, 4 parts of magnesium oxide, 4 parts of silicon carbide whiskers, 3 parts of borax, 3.5 parts of composite antibacterial agent, 40 parts of water were mixed evenly, and wet ball milled at a speed of 650r / min for 5h to obtain body slurry, which was then pressed into shape and dried to obtain a ceramic body;
[0044] S4, preparation of glaze slurry: 42 parts of potassium feldspar, 30 parts of sodium feldspar, 25 parts of quartz, 6 parts of magnesite, 13 parts of calcite, 10 parts of zinc oxide, 12 parts of illite, 7 parts of talc, 9 parts of zirconium silicate, 4 parts of composite antibacterial agent, 5 parts of sodium carboxymethyl cellulose, and 80 parts of water were mixed evenly, and wet ball milled at a speed of 850 r / min for 7.5 h to obtain glaze slurry;
[0045] S5, glazing and sintering: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping to obtain a glaze layer with a thickness of 0.7 mm. After drying at 105°C, sintering is performed. The sintering process is as follows: in an inert atmosphere, heating to 450°C at a heating rate of 4°C / min, keeping the temperature for 3 hours, then heating to 1230°C at a heating rate of 7°C / min for 4 hours, and naturally cooling to obtain the antibacterial ceramic. Example 3
[0046] A method for preparing an antibacterial ceramic, characterized in that it comprises the following steps:
[0047] S1. Preparation of composite hydroxyapatite: Na2HPO4 was added to deionized water, and then ammonia water with a mass concentration of 15% was added to adjust the pH to 11 to obtain a solution A with a concentration of 0.5 mol / L; Ca(NO3)2 was added to deionized water to obtain a solution B with a concentration of 0.8 mol / L; 180 mL of solution B was added dropwise to 300 mL of solution A under stirring conditions (stirring speed was 100 r / min), and ammonia water was added during the addition to maintain the pH at 10. After the addition was completed, 90 mL of 0.1 mol / L tetrabutyl titanate ethanol solution was added, and the mixture was hydrothermally reacted at 130°C for 8 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain composite hydroxyapatite;
[0048] S2. Preparation of composite antibacterial agent: 50g of composite hydroxyapatite was added to 900mL of ethanol aqueous solution (volume concentration of ethanol was 60%), followed by adding 10g of γ-aminopropyltriethoxysilane, stirring and reacting at 65°C for 2h, adding 5g of 5-thiazolecarboxaldehyde and 20g of triethylamine after the reaction was completed, and reacting at a constant temperature of 70°C in a nitrogen atmosphere for 3h, filtering, washing and drying after the reaction was completed to obtain a solid product; then, 50g of the solid product was added to 800g of deionized water, followed by adding 5g of silver nitrate and 3g of copper nitrate, adjusting the pH to 6, and chelating the reaction at 70°C for 7h, filtering and drying after the reaction was completed, and calcining at 600°C in a nitrogen atmosphere for 2h to obtain a composite antibacterial agent;
[0049] S3, preparation of ceramic body: by weight, 30 parts of kaolin, 20 parts of quartz, 15 parts of dolomite, 10 parts of aluminum oxide, 2 parts of potassium carbonate, 1 part of calcium carbonate, 5 parts of diatomaceous earth, 3 parts of magnesium oxide, 3 parts of silicon carbide whiskers, 2 parts of borax, 3 parts of composite antibacterial agent, 35 parts of water were mixed evenly, and wet-milled at a speed of 600 r / min for 6 hours to obtain a body slurry, which was then pressed into shape and dried to obtain a ceramic body;
[0050] S4, preparation of glaze slurry: 40 parts of potassium feldspar, 25 parts of sodium feldspar, 20 parts of quartz, 5 parts of magnesite, 10 parts of calcite, 8 parts of zinc oxide, 10 parts of illite, 5 parts of talc, 8 parts of zirconium silicate, 3 parts of composite antibacterial agent, 4 parts of sodium carboxymethyl cellulose, and 70 parts of water were mixed evenly, and wet ball milled at a speed of 800 r / min for 8 hours to obtain glaze slurry;
[0051] S5, glazing and sintering: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping to obtain a glaze layer with a thickness of 0.7 mm. After drying at 100°C, sintering is performed. The sintering process is as follows: in an inert atmosphere, the temperature is increased to 400°C at a rate of 3°C / min, and the temperature is kept for 4 hours. Then, the temperature is increased to 1200°C at a rate of 6°C / min for 5 hours. After natural cooling, the antibacterial ceramic is obtained. Example 4
[0052] A method for preparing an antibacterial ceramic, characterized in that it comprises the following steps:
[0053] S1. Preparation of composite hydroxyapatite: Na2HPO4 was added to deionized water, and then 15% ammonia water was added to adjust the pH to 12 to obtain a solution A with a concentration of 0.7 mol / L; Ca(NO3)2 was added to deionized water to obtain a solution B with a concentration of 1 mol / L; 210 mL of solution B was added dropwise to 360 mL of solution A under stirring (stirring speed was 130 r / min), and ammonia water was added during the addition to keep the pH at 11. After the addition was completed, 120 mL of 0.15 mol / L tetrabutyl titanate ethanol solution was added, and the mixture was hydrothermally reacted at 140°C for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain composite hydroxyapatite;
[0054] S2. Preparation of composite antibacterial agent: 60g composite hydroxyapatite was added to 900mL ethanol aqueous solution (volume concentration of ethanol was 70%), followed by adding 13g γ-aminopropyltriethoxysilane, stirring and reacting at 70°C for 1h, adding 7g 5-thiazolecarboxaldehyde and 25g triethylamine after the reaction was completed, and reacting at a constant temperature of 75°C in a nitrogen atmosphere for 2h, filtering, washing and drying after the reaction was completed to obtain a solid product; then, 60g of the solid product was added to 900g deionized water, followed by adding 8g silver nitrate and 5g copper nitrate, adjusting the pH to 6.5, and chelating reaction was carried out at 80°C for 5h, filtering and drying after the reaction was completed, and calcining at 700°C in a nitrogen atmosphere for 1h to obtain a composite antibacterial agent;
[0055] S3, preparation of ceramic body: by weight, 40 parts of kaolin, 25 parts of quartz, 20 parts of dolomite, 15 parts of aluminum oxide, 3 parts of potassium carbonate, 2 parts of calcium carbonate, 8 parts of diatomaceous earth, 6 parts of magnesium oxide, 5 parts of silicon carbide whiskers, 5 parts of borax, 4 parts of composite antibacterial agent, 45 parts of water were mixed evenly, and wet-milled at a speed of 700 r / min for 4 hours to obtain a body slurry, which was then pressed into shape and dried to obtain a ceramic body;
[0056] S4, preparation of glaze slurry: 45 parts of potassium feldspar, 35 parts of sodium feldspar, 30 parts of quartz, 8 parts of magnesite, 15 parts of calcite, 12 parts of zinc oxide, 14 parts of illite, 10 parts of talc, 11 parts of zirconium silicate, 5 parts of composite antibacterial agent, 6 parts of sodium carboxymethyl cellulose, and 90 parts of water were mixed evenly, and wet-milled at a speed of 900 r / min for 7 hours to obtain glaze slurry;
[0057] S5, glazing and sintering: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping to obtain a glaze layer with a thickness of 0.7 mm. Dry it at 110°C and then sinter it. The sintering process is as follows: in an inert atmosphere, heat up to 500°C at a heating rate of 5°C / min, keep it warm for 2 hours, then heat up to 1250°C at a heating rate of 8°C / min for 3 hours, and obtain the antibacterial ceramic after natural cooling. Comparative Example 1
[0058] A method for preparing an antibacterial ceramic comprises the following steps:
[0059] S1. Preparation of hydroxyapatite: Na2HPO4 was added to deionized water, and then 15% ammonia water was added to adjust the pH to 12 to obtain a solution A with a concentration of 0.6 mol / L; Ca(NO3)2 was added to deionized water to obtain a solution B with a concentration of 0.9 mol / L; 200 mL of solution B was added dropwise to 330 mL of solution A under stirring conditions (stirring speed was 120 r / min), and ammonia water was added during the addition to maintain the pH at 11. After the addition was completed, the solution was hydrothermally reacted at 135°C for 7 hours. After the reaction was completed, the solution was filtered, washed, and dried to obtain hydroxyapatite;
[0060] S2. Preparation of composite antibacterial agent: 55 g of hydroxyapatite was added to 900 mL of ethanol aqueous solution (the volume concentration of ethanol was 65%), and then 12 g of γ-aminopropyltriethoxysilane was added, and the mixture was stirred and reacted at 70°C for 1 h. After the reaction was completed, 6 g of 5-thiazolecarboxaldehyde and 23 g of triethylamine were added, and the mixture was kept at 73°C in a nitrogen atmosphere for 2.5 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a solid product. Subsequently, 55 g of the solid product was added to 850 g of deionized water, and then 7 g of silver nitrate and 4 g of copper nitrate were added to adjust the pH to 7, and the mixture was chelated at 75°C for 6 h. After the reaction was completed, the mixture was filtered, dried, and calcined at 650°C in a nitrogen atmosphere for 1.5 h to obtain a composite antibacterial agent.
[0061] S3, preparation of ceramic body: by weight, 35 parts of kaolin, 23 parts of quartz, 17 parts of dolomite, 13 parts of aluminum oxide, 2.5 parts of potassium carbonate, 1.5 parts of calcium carbonate, 7 parts of diatomaceous earth, 5 parts of magnesium oxide, 4 parts of silicon carbide whiskers, 4 parts of borax, 3.5 parts of composite antibacterial agent, 40 parts of water were mixed evenly, and wet ball milled at a speed of 650r / min for 5h to obtain body slurry, which was then pressed into shape and dried to obtain a ceramic body;
[0062] S4, preparation of glaze slurry: 43 parts of potassium feldspar, 30 parts of sodium feldspar, 25 parts of quartz, 7 parts of magnesite, 12 parts of calcite, 10 parts of zinc oxide, 12 parts of illite, 8 parts of talc, 10 parts of zirconium silicate, 4 parts of composite antibacterial agent, 5 parts of sodium carboxymethyl cellulose, and 80 parts of water were mixed evenly, and wet ball milled at a speed of 850 r / min for 7.5 h to obtain glaze slurry;
[0063] S5, glazing and sintering: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping to obtain a glaze layer with a thickness of 0.7 mm. After drying at 105°C, sintering is performed. The sintering process is as follows: in an inert atmosphere, heating to 450°C at a heating rate of 4°C / min, keeping the temperature for 3 hours, then heating to 1230°C at a heating rate of 7°C / min for 4 hours, and naturally cooling to obtain the antibacterial ceramic.
[0064] Compared with Example 1, titanium dioxide is not introduced on hydroxyapatite in this comparative example. Comparative Example 2
[0065] A method for preparing an antibacterial ceramic comprises the following steps:
[0066] S1. Preparation of composite hydroxyapatite: Na2HPO4 was added to deionized water, and then ammonia water with a mass concentration of 15% was added to adjust the pH to 12 to obtain a solution A with a concentration of 0.6 mol / L; Ca(NO3)2 was added to deionized water to obtain a solution B with a concentration of 0.9 mol / L; 200 mL of solution B was added dropwise to 330 mL of solution A under stirring conditions (stirring speed was 120 r / min), and ammonia water was added during the addition to maintain the pH at 11. After the addition was completed, 110 mL of 0.13 mol / L tetrabutyl titanate ethanol solution was added, and the mixture was hydrothermally reacted at 135°C for 7 hours. After the reaction was completed, the mixture was filtered, washed, and dried to obtain composite hydroxyapatite;
[0067] S2, preparation of composite antibacterial agent: 55g composite hydroxyapatite was added to 850g deionized water, followed by 7g silver nitrate and 4g copper nitrate, the pH was adjusted to 7, chelation reaction was carried out at 75°C for 6h, after the reaction was completed, it was filtered and dried, and calcined at 650°C for 1.5h in a nitrogen atmosphere to obtain a composite antibacterial agent;
[0068] S3, preparation of ceramic body: by weight, 35 parts of kaolin, 23 parts of quartz, 17 parts of dolomite, 13 parts of aluminum oxide, 2.5 parts of potassium carbonate, 1.5 parts of calcium carbonate, 7 parts of diatomaceous earth, 5 parts of magnesium oxide, 4 parts of silicon carbide whiskers, 4 parts of borax, 3.5 parts of composite antibacterial agent, 40 parts of water were mixed evenly, and wet ball milled at a speed of 650r / min for 5h to obtain body slurry, which was then pressed into shape and dried to obtain a ceramic body;
[0069] S4, preparation of glaze slurry: 43 parts of potassium feldspar, 30 parts of sodium feldspar, 25 parts of quartz, 7 parts of magnesite, 12 parts of calcite, 10 parts of zinc oxide, 12 parts of illite, 8 parts of talc, 10 parts of zirconium silicate, 4 parts of composite antibacterial agent, 5 parts of sodium carboxymethyl cellulose, and 80 parts of water were mixed evenly, and wet ball milled at a speed of 850 r / min for 7.5 h to obtain glaze slurry;
[0070] S5, glazing and sintering: glaze the glaze slurry in step S4 on the surface of the ceramic body in step S3 by dipping to obtain a glaze layer with a thickness of 0.7 mm. After drying at 105°C, sintering is performed. The sintering process is as follows: in an inert atmosphere, heating to 450°C at a heating rate of 4°C / min, keeping the temperature for 3 hours, then heating to 1230°C at a heating rate of 7°C / min for 4 hours, and naturally cooling to obtain the antibacterial ceramic.
[0071] Compared with Example 1, this comparative example does not introduce 5-thiazolecarboxaldehyde into the composite hydroxyapatite.
[0072] The antibacterial ceramics prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, as follows: wear resistance was tested according to GB / T 3810.7-2016 "Test methods for ceramic tiles - Part 7: Determination of surface wear resistance of glazed tiles"; the bending strength of the samples was tested using a universal material testing machine, with a sample size of 3mm×4mm×20mm, a span of 16mm, a pressure head loading speed of 0.5mm / min, and the bending strength was the average of three measurement results; antibacterial performance test: the antibacterial performance of ceramic products against Escherichia coli was tested in accordance with the standard of JC / T 897-2014; antibacterial durability test: the antibacterial durability of ceramic products against Escherichia coli was tested in accordance with the standard of JC / T 897-2014, and the test results are shown in Table 1 below.
[0073] Table 1
[0074]
[0075] It can be seen from Table 1 above that the antibacterial ceramics prepared by the present invention have good strength, wear resistance and antibacterial properties, and also have good antibacterial durability, which ensures its reliability and stability in various application scenarios and has great application prospects.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an antibacterial ceramic, characterized in that: The following steps are involved: S1. Add Na2HPO4 to deionized water, and then add ammonia water to adjust the pH to 11-12 to obtain solution A; add Ca(NO3)2 to deionized water to obtain solution B; add solution B dropwise to solution A under stirring, add ammonia water during the addition to keep the pH at 10-11, add tetrabutyl titanate ethanol solution after the addition is completed, perform hydrothermal reaction, filter, wash and dry after the reaction is completed to obtain composite hydroxyapatite; S2, adding composite hydroxyapatite to an ethanol aqueous solution, then adding γ-aminopropyltriethoxysilane, stirring to react, adding 5-thiazolecarboxaldehyde and triethylamine after the reaction is completed, and reacting at a constant temperature under a nitrogen atmosphere, filtering, washing, and drying after the reaction is completed to obtain a solid product; then adding the solid product to deionized water, then adding silver nitrate and copper nitrate, adjusting the pH to 6-7, and performing a chelating reaction, filtering, drying, and calcining after the reaction is completed to obtain a composite antibacterial agent; S3, kaolin, quartz, dolomite, alumina, potassium carbonate, calcium carbonate, diatomaceous earth, magnesium oxide, silicon carbide whisker, borax, composite antibacterial agent, and water are uniformly mixed, wet ball milled to obtain green body slurry, then pressed into shape, and dried to obtain a ceramic green body; S4, mixing potassium feldspar, sodium feldspar, quartz, magnesite, calcite, zinc oxide, illite, talc, zirconium silicate, composite antibacterial agent, sodium carboxymethyl cellulose and water uniformly, and performing wet ball milling to obtain glaze slurry; S5, applying the glaze slurry in step S4 to the surface of the ceramic body in step S3 by dipping to obtain a glaze layer, drying and then sintering, and naturally cooling to obtain the antibacterial ceramic.
2. The preparation method according to claim 1, characterized in that: In step S1, the concentration of solution A is 0.5-0.7 mol / L, the concentration of solution B is 0.8-1 mol / L, the mass concentration of ammonia water is 10-15%, the concentration of tetrabutyl titanate ethanol solution is 0.1-0.15 mol / L, and the volume ratio of solution A, solution B, and tetrabutyl titanate ethanol solution is 180-210:300-360:90-120.
3. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step S1 is 130-140° C. and the time is 6-8 hours.
4. The preparation method according to claim 1, characterized in that: The volume concentration of ethanol in the ethanol aqueous solution in step S2 is 60-70%, the mass ratio of the composite hydroxyapatite, γ-aminopropyltriethoxysilane, 5-thiazolecarboxaldehyde, and triethylamine is 50-60:10-13:5-7:20-25, the temperature of the stirring reaction is 65-70°C, the time is 1-2h, and the temperature of the constant temperature reaction is 70-75°C, and the time is 2-3h.
5. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the solid product, deionized water, silver nitrate and copper nitrate is 50-60:800-900:5-8:3-5, the temperature of the chelating reaction is 70-80°C, and the time is 5-7h; the temperature of the calcination is 600-700°C, and the time is 1-2h.
6. The preparation method according to claim 1, characterized in that: In step S3, the amount of each raw material is as follows, by weight: 30-40 parts of kaolin, 20-25 parts of quartz, 15-20 parts of dolomite, 10-15 parts of aluminum oxide, 2-3 parts of potassium carbonate, 1-2 parts of calcium carbonate, 5-8 parts of diatomaceous earth, 3-6 parts of magnesium oxide, 3-5 parts of silicon carbide whiskers, 2-5 parts of borax, 3-4 parts of composite antibacterial agent, and 35-45 parts of water; the rotation speed of the wet ball mill is 600-700r / min, and the time is 4-6h.
7. The preparation method according to claim 1, characterized in that: In step S4, the amount of each raw material is as follows, by weight: 40-45 parts of potassium feldspar, 25-35 parts of sodium feldspar, 20-30 parts of quartz, 5-8 parts of dolomite, 10-15 parts of calcite, 8-12 parts of zinc oxide, 10-14 parts of illite, 5-10 parts of talc, 8-11 parts of zirconium silicate, 3-5 parts of composite antibacterial agent, 4-6 parts of sodium carboxymethyl cellulose, and 70-90 parts of water; the rotation speed of the wet ball mill is 800-900r / min, and the time is 7-8h.
8. The preparation method according to claim 1, characterized in that: The thickness of the glaze layer in step S5 is 0.5-0.8 mm.
9. The preparation method according to claim 1, characterized in that: The sintering process in step S5 is: in an inert atmosphere, heating up to 400-500°C at a heating rate of 3-5°C / min, keeping the temperature for 2-4h, and then heating up to 1200-1250°C at a heating rate of 6-8°C / min for 3-5h.
10. An antibacterial ceramic prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Antibacterial ceramic glaze, and preparation method and application thereof
CN110818261A
Environment-friendly antibacterial ceramic blank and processing technology thereof
CN113213903A
Highlight antibacterial ceramic tile and production process thereof
CN115321949A
Composite friction agent with surface uniformly coated with silver-loaded nano-hydroxyapatite as well as preparation method and application of composite friction agent
CN118078684A